INVESTIGATION OF SOME NON-STEROIDAL COMPLEXES - Amira J. Al_Shaheen; Miaad A. Al Mula (Journals Park Publishing, 2022)
In this study we describe the synthesis and characterization of four and six coordinated compounds of Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) with diclofenacyl hydrazide and vanillin or acetophenone ligands (L1andL2).These complexes were characterized by many physicochemical methods such as elemental analysis (CHN),magnetic susceptibility, molar conductance as well as spectral studies such as IR and UV-Visible , and X-ray powder diffraction measurementsT. The ligands have been investigated by NMR spectra,. Furthermore, the complexes have been found to have the formulaes : [M(L)2Cl2] where, M= Co(II) , Ni(II) , Cu(II) and Zn(II), whereas, the formula [M(L)2(H2O)2]X2 , M= Co(II) , Ni(II) , Cu(II) and Zn(II), X= NO3- , Cl- . [M(L)2]X2 , where, M= Ni(II) , Cu(II) and Cd(II), X= NO3- , Cl- . L = L1 or L2 . Infrared spectral data suggest that the two ligands behave as a bidentate ligand with O,N, donor atoms towards the metal ions. On the basis of the above physicochemical measurements, the complexes have an octahedral and tetrahedral or square planar geometries.
Keywords: X-ray powder diffraction; Metal complexes; diclofenacyl Complexes